The NexStar Evolution and SkyPortal User's Guide - Chen, James L.; Chen, Adam (The Patrick Moore Practical Astronomy Series, 2016)
This book serves as a comprehensive guide for using a Nexstar Evolution mount with WiFi SkyPortal control, walking the reader through the process for aligning and operating the system from a tablet or smartphone. The next generation Go-To mount from Celestron, this is compatible not only with the Nextstar Evolution but also with older mounts. It is the ideal resource for anyone who owns, or is thinking of owning, a Nexstar Evolution telescope, or adapting their existing Celestron mount. Pros and cons of the system are thoroughly covered with a critical depth that addresses any possible question by users. Beginning with a brief history of Go-To telescopes and the genesis of this still new technology, the author covers every aspect of the newly expanding capability in observing. This includes the associated Sky Portal smartphone and tablet application, the transition from the original Nexstar GoTo system to the new SkyPortal system, the use of the Sky Portal application with its Sky Safari 4 basic software and Celestron WiFi adaptations, and discussions on the use of SkyPortal application using the Celestron adapter on older Celestron mounts. Comments and recommendations for equipment enable the reader to successfully use and appreciate the new WiFi capability without becoming overwhelmed. Extensively illustrated using actual screenshots from the program interface, this is the only guide to the Nextstar SkyPortal an observer will need.